Kadar Estrogen dan Munculnya Estrus setelah Pemberian Buserelin (Agonis GnRH) pada Sapi Bali yang Mengalami Anestrus Postpartum Akibat Hipofungsi Ovarium - Ni Ketut Suartini; I Gusti Ngurah Bagus Trilaksana; Tjok Gde Oka Pemayun (Veterinary Science and Medicine Journal, 2013)
The purpose of this study was to measure the levels of estrogen and the onset of estrous after administration of Buserelin on bali cattle experiencing anestrous postpartum due to ovarian hypofunction. This research used twenty seven bali cattles which were divided evenly into three groups of treatment, namely group-one as control group (P0, without treatment), group-two, receiving a single injection of Buserelin at dose of 0.02 mg (P1) and group three, receiving repeated injection of Buserelin at dose of 0.02 mg at 24 hours interval (P3). Serum estrogen levels were measured at a time off before estrous, a time of estrous, and five days after the onset of estrous using ELISA method. Data were analyzed using statistical analysis of variance and a Duncan’s Multiple Range Test for a further analysis. The results showed that at the stage of estrous, the estrogen level of P0 was lower significantly (p<0.05) than two others treatments (P1 and P2), but those of P1 and P2 were statistically the same (p>0.05). The onset of estrous on P2 was shorter than those of P1 (p<0.05). It can be concluded that the administration of Buserelin can trigger an estrous on Bali cattle that experiencing anestrous postpartum due to ovarian hypofunction and repeated administrations of Buserelin can shorten the onset of estrous.